2009
DOI: 10.1177/1066896909336441
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Malignancies With Cytologically Negative Pleural and Peritoneal Effusions: Demons’ or Meigs’ Pseudo-syndromes?

Abstract: The authors reviewed the original reports of the association of malignant ovarian tumors with cytologically negative pleural and peritoneal effusions, commonly known as Meigs' pseudo-syndrome and challenged the recent attribution of this disease to Demons. They underlined the historical and clinical interest of the reports of Demons and Meigs and concluded that the term pseudo-Meigs' syndrome, and not pseudo-Demons' syndrome, must be used for malignant ovarian lesions with effusions with negative cytology beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…By definition, lack of evidence for peritoneal or pleural spread of the tumor must have been documented (negative pleural and peritoneal fluid cytology and/or no malignant involvement in biopsy samples) and both ascites and hydrothorax should have resolved after tumor removal. 15,23,24 …”
Section: Methodsmentioning
confidence: 99%
“…By definition, lack of evidence for peritoneal or pleural spread of the tumor must have been documented (negative pleural and peritoneal fluid cytology and/or no malignant involvement in biopsy samples) and both ascites and hydrothorax should have resolved after tumor removal. 15,23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Other benign cysts of the ovary (such as struma ovarii, mucinous cystadenoma and teratomas), leiomyoma of the uterus, and secondary metastatic tumours to ovary if associated with hydro thorax are referred to as ‘Pseudo‐Meigs” syndrome 6 …”
Section: Introductionmentioning
confidence: 99%
“…Meigs' syndrome stands in contrast to pseudo-Meigs, which presents with ascites and pleural effusion in association with benign tumors of the ovary (other than fibromas) and malignant tumors. Benign tumors in this category include mucinous cystadenomas, teratomas, struma ovarii, and leiomyomas [3]. Although it is difficult to determine the incidence of Meigs' syndrome, it has been reported that 0.20 per 100,000 women are diagnosed with ovarian sex cord stromal tumors (SCST) [4].…”
Section: Introductionmentioning
confidence: 99%